(untitled) (One Health & Risk Management, 2023)
Introduction. Road traffic injuries are a significant issue for society in the twenty-first century, but public health experts frequently ignore them despite the fact that massive and coordinated efforts are required for their effective and long-term prevention. Human factors and poor driving performance are the most significant contributors to car accidents globally, as shown by a series of studies exploring the causes of traffic road accidents. Since road safety is a key concern in developing countries, our research focuses on the car driver behavioral risk factors in the Republic of Moldova. Material and methods. A cross-sectional quantitative descriptive using a questionnaire was applied online via a Google form document among car drivers, between January-March 2022. Microsoft Excel was used for the statistical analyses. Results. The questionnaire was completed by 257 respondents above 18 years, of which 61.9% were female and 38.1% were male, mostly with a category B license (73.5%) and majority from urban area (87.5%). More than half (55.6%) mention that drove a car daily and 30% of them have a drive experience of more than ten years. Respondents express great concern (71.2%) about the issue of traffic accidents, and 76.3% think that unsafe roads are a key contributing factor. At least once being involved as a driver in road accidents where medical care was needed was mentioned by 2.7% of respondents. Conclusions. Educational programs and awareness campaigns about road safety among drivers and other vulnerable road users should be systematically organized.